A thermographic technique for in-plane thermal diffusivity measurement of electroplated coatings. (May 2019) - Genna, S.; Ucciardello, N.
Graphical abstract: Highlights: A thermographic procedure was developed for the in-plane thermal diffusivity. The technique is effective for the in-plane thermal diffusivity of thin coatings. The coating allows an increase of about 45% in thermal diffusivity of the aluminium. Abstract: In the present work, a thermographic procedure is developed and tested with the aim to determine the in-plane thermal diffusivities of electroplated coatings with different thickness on an aluminium alloy (AA6082). For the tests, a single pulse of a diode laser source was adopted to generate a thermal contrast on the specimen's surface. An infrared camera was adopted to acquire the surface gradient temperature and a MATLAB algorithm was developed to calculate the thermal diffusivity. In order to study the influence of the laser parameters set on the technique, two different laser pulses were adopted to heat the specimens; moreover, the influence of the starting acquiring time by IR camera was also evaluated. From the results, the technique is demonstrated to be effective for the in-plane thermal diffusivity measurement of thin coatings and, within the investigated parameters window, to be not affected by the checked parameters.